Development of the Marine Protected Area Network in the Argentine Islands area (Akademik Vernadsky Antarctic Station, Ukraine) - Utevsky, A.Y.; Kolesnykova, M.Y.; Shmyrov, D.V.; Sinna, О.I. (Український антарктичний журнал, 2014)
Based on underwater observations the establishment of marine protected areas in the Stella Creek and Skua Creek straits were proposed. Selection of areas was carried out in accordance with the protocol NAGISA and acoustic bottom survey of the Argentine Islands water area. Descriptions of the marine protected areas were developed and their categories according to IUCN methodology were defined. Сompliance indices calculated according to the IUCN methodology assign the Stella Creek and the Skua Creek MPAs to the IUCN protected categories Ia and III, respectively. 3D models of the marine protected areas were designed. За результатами підводних спостережень відповідно до протоколу NAGISA та акустичних досліджень дна в акваторії Аргентинських островів запропоновано утворення морських охоронюваних районів у протоках Stella Creek та Skua Creek. Розраховані за методикою IUCN індекси відповідності для МОР свідчать, що протоки Stella Creek та Skua Creek слід віднести до природоохоронних категорій Ia та III відповідно. Розроблено описи морських охоронюваних районів. Розроблено 3D моделі морських охоронюваних районів. На основании подводных наблюдений в соответствии с протоколом NAGISA и акустических исследований дна в акватории Аргентинских островов предложено создание морских охраняемых районов в проливах Stella Creek и Skua Creek. По результатам расчетов, по методологии IUCN, МОР Stella Creek и Skua Creek отнесены к природоохранным категориям Ia и III соответственно. Разработаны описания морских охраняемых районов. Разработаны 3D модели морских охраняемых районов. This work was supported by the Public Institution Ukrainian Antarctic Scientific Center, using data obtained during Ukrainian Antarctic Expeditions at Ukrainian Antarctic Vernadsky station.